Kendala Penerapan Kurikulum 2013 dalam Pembelajaran Fisika Di SMA Kabupaten Kotabaru - Muhammad Ali (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2020)
The general objective of this research is to describe the constraints of high school teachers in applying the 2013 Curriculum in Physics learning in Kotabaru District and the specific objectives of selecting lesson plans, understanding learning activities and understanding learning principles. This research method is descriptive data analysis with the object of research of high school physics teachers in Kotabaru Regency and this study is a qualitative study. The research data was obtained through observation / interviews and teacher responses questionnaire. The results of the study show: (1) 25.53% Teachers are still constrained by the preparation of lesson plans, especially in various learning sources (open texts, internet, natural and social environment), varied learning media, media that are compatible with learning material, scientific learning approaches, (2) 25.25% Teachers are still constrained in implementing learning activities which include the delivery of competencies to be achieved to students, have not carried out contextual and scientific learning, have not facilitated students to analyze information to make conclusions, have not used varied learning media, ( 3) 36.71% Teachers are constrained to understand the principle of learning mainly related to differences in textual approaches with scientific approaches, differences in partial learning with integrated learning, learning differences that emphasize single answers with learning that requires multi-dimensional answers, and differences in learning of verbalism with learning. applicable learning. Keywords: Teacher Constraints, 2013 Curriculum, Scientific.